...y no se lo tragó la tierra - Rivera, Tomás, 1935-1984 (Arte Público Press, 2015)
"I tell you, God could care less about the poor. Tell me, why must we live here like this? What have we done to deserve this? You're so good and yet you suffer so much," a young boy tells his mother in Tomás Rivera's classic novel about the migrant worker experience. Outside the chicken coop that is their home, his father wails in pain from the unbearable cramps brought on by sunstroke after working in the hot fields. The young boy can't understand his parents' faith in a god that would impose such horrible suffering, poverty and injustice on innocent people.Adapted into the award-winning film ...And the earth did not swallow him and recipient of the first award for Chicano literature, the Premio Quinto Sol, in 1970, Rivera's masterpiece recounts the experiences of a Mexican-American community through the eyes of a young boy. Forced to leave their home in search of work, the migrants are exploited by farmers, shopkeepers, even other Mexican Americans, and the boy must forge his identity in the face of exploitation, death and disease, constant moving and conflicts with school officials.In this new edition of a powerful novel comprised of short vignettes, Rivera writes hauntingly about alienation, love and betrayal, man and nature, death and resurrection and the search for community.